2004
DOI: 10.1111/j.1398-9995.2003.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of storage mite sensitization in a general adult population

Abstract: SMs (T. putrescentiae and L. destructor) are major aeroallergens in adults in the region studied, even in subjects without occupational exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 23 publications
3
57
0
2
Order By: Relevance
“…These results are consistent with those observed for the allergic human population of Galicia, where sensitisation to storage mites (86%) is more prevalent than sensitisation to D. pteronyssinus (50.4%), which was traditionally considered the main allergen in Galicia (Vidal et al, 2004). …”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with those observed for the allergic human population of Galicia, where sensitisation to storage mites (86%) is more prevalent than sensitisation to D. pteronyssinus (50.4%), which was traditionally considered the main allergen in Galicia (Vidal et al, 2004). …”
Section: Discussionsupporting
confidence: 90%
“…Only patients sensitized to HDM and with symptoms of HDM were included. Patients with positive SPT results for Dermatophagoides also underwent SPTs for L destructor, which is highly prevalent in the region [6][7][8].…”
Section: Study Populationmentioning
confidence: 99%
“…Active smoking may even impair responsiveness to therapeutic intervention with corticosteroids (19 -21). Other studies, however, have either failed to find such associations (22)(23)(24) or have found smokers to be at significantly lower risk of developing asthma compared with nonsmokers and ex-smokers (24,25). Indeed, Hjern et al (26) have shown that cigarette smoke may in fact attenuate the development of allergic responses, as indicated by an inverse correlation between the prevalence of allergic asthma or rhinoconjunctivitis and the number of cigarettes smoked.…”
mentioning
confidence: 99%